Praktik Kesalehan Umat Melalui Devosi Kepada Bunda Maria di Stasi Santa Maria Maluhu Paroki St. Pius X Tenggarong - Ferdinandus Edison Musi; Wilfridus Samdirgawijaya; Zakeus Daeng Lio (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2021)
This study aims to determine the practice of devotion to St. Marry at Santa Maria Maluhu Station, Paroki St. Pius X Tenggarong, what devotional practices to Our Lady have been done by the people in Santa Maria Maluhu Station and how to implement it. This research was conducted at St. Maria Maluhu Parish of Santo Pius X Tenggarong by using qualitative descriptive methods and data collection techniques used were interviews, observation, documentation and document studies. The informants in this study were the head of the Leader community, the liturgical division, the people, and the head of the Neighborhood Association. Popular piety of the people through Devotion to the Virgin Mary carried out by Catholics at the Santa Maria Maluhu Station, namely the Hail Mary Prayer, Pilgrimage to the Cave of Mary, Imitating the Virgin Mary through social example, the Rosary Prayer, and the Novena Prayer. The results of research on devotion to the Virgin Mary that have been carried out by Catholics at the Santa Maria Maluhu station in its implementation in accordance with the recommendations of the Catholic Church, this is proven because there is no practice of extremism and minimalism at the Santa Maria Maluhu